Strategi Pembelajaran Band Berbasis Industri Kreatif di SMK N 3 Banyumas - Tantia Wahyu Kinanti; Agus Cahyono; Muh Fakhrun Na’am (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to examine how the band learning process aligns with the competency requirements in the creative music industry. A qualitative approach was used with teachers and students of the music program at SMK N 3 Banyumas as subjects. Data was collected through observation, documentation, and interviews, then validated using triangulation techniques and sources. Initial findings indicate that the values of creativity, cooperation, and technical musical skills have been integrated into band learning at this school and are in line with the needs of the creative industry. Teachers encourage teamwork, a professional attitude, and adaptation to developments in the contemporary music industry. However, management and the use of digital technology as a medium for music production and distribution remain challenges. Therefore, band learning at SMK N 3 Banyumas is considered highly relevant to the needs of the creative industry. However, in order for students to be able to compete professionally in today's music industry, strengthening of managerial and digital literacy aspects is needed.